Analisis Permasalahan Saluran Drainase Di Desa Jeumpet Ajuen Kecamatan Darul Imarah Aceh Besar - Alhabib, Syaidinulla; Ziana, Ziana; Refika, Cut Dwi; Shaskia, Nina (Journal of The Civil Engineering Student, 2024)
Floods often hit Aceh Province, especially in Aceh Besar District, Jeumpet Ajuen Village, Darul Imarah District. The main cause of flooding is high rainfall intensity which causes drainage channels to be unable to accommodate water discharge. This study aims to determine the flood discharge, the existing capacity of the channel, and the condition of the drainage channel based on the flood discharge and the existing capacity. The channel under review is the primary channel in Jeumpet Ajuen Village. Primary data was obtained through direct measurement of drainage channel dimensions, while secondary data was in the form of maximum daily rainfall from three rainfall stations in Aceh Besar District. The method used is the modified rational method for hydrological analysis and the HEC-RAS 6.0 application for hydraulic analysis. Data on planned flood discharge and existing dimensions were inputted into HEC-RAS. The discharges entered were discharges with a return period of 5 years and 10 years. HEC-RAS results showed that all review points experienced runoff, especially the left channel with runoff ranging from 0,99 meters to 3,65 meters for a 10-year return period. The existing capacity of the drainage channel is greater than the planned flood discharge, which is Qs = 14,797 m3/det greater than Qt = 9,248 m3/det. However, the existing capacity experiences runoff because the channel discharge is very large for the existing channel dimensions.